Implementasi Permainan Quiz Team untuk Meningkatkan Daya Ingat Mufrodat Bahasa Arab - Kholisoh Qatrun Nada; Yayah Robiatul Adawiyah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2026)
Arabic mufrodat learning at LPBA is still dominated by direct memorization methods that tend to be monotonous, causing students to become easily bored and to have difficulty retaining memorization in the long term. Although the Quiz Team game has been used in learning, studies that specifically implement a three-round-based model, namely isyarah, kalam, and tahrik, remain limited. This study aims to describe the implementation of the Quiz Team game in improving Arabic mufrodat memory retention at LPBA of Nurul Jadid Islamic Boarding School. This study used a descriptive qualitative approach with a case study design. Data were collected through observation, semi-structured interviews with teachers, LPBA administrators, and students, as well as documentation. The results show that the implementation of the Quiz Team game was carried out through three rounds, namely isyarah, kalam, and tahrik, combined with the use of flashcards and group cooperation. The learning process included the stages of planning, implementation, and formative evaluation. This game was able to improve mufrodat memory retention, learning motivation, and students’ active engagement. Supporting factors included students’ enthusiasm, variation in game rounds, group collaboration, and teacher support, while the obstacles encountered included limited time, difficulty in demonstrating abstract mufrodat, student absence, and the emergence of new mufrodat that had not yet been taught. This study confirms that the three-round-based Quiz Team game is effective in improving Arabic mufrodat memory retention and creating more interactive and enjoyable learning. The implications of this study indicate that the Quiz Team game can be used as an alternative strategy for mufrodat learning that is innovative, interactive, student-centered, and potentially applicable in broader Arabic language learning contexts.